The Church at Nanrantsouak: Sébastien Râle, S.J., and the Wabanaki of Maine's Kennebec River - Clark, William A. (The catholic historical review, 2006)
French Jesuit Sébastien Râle arrived in Canada in 1689 and was missioned to the Wabanaki natives of the Kennebec River in what is now Maine. Râle accompanied the Wabanaki for thirty years, eventually dying with many of them during an English raid on their principal village, Nanrantsouak ("Norridgewock"). For three centuries, Râle's reputation, for good and ill, has depended primarily on perceptions of his role in the geopolitical and religious rivalries of the Europeans. The initiative of the Wabanaki themselves has usually been ignored. The author references recent scholarship from the native viewpoint, and original documentary sources, in an attempt to take the Wabanaki seriously as a local church—a community of Christians who, through the particular emphases of Râle's missionary method, came both to embrace Christianity and to make it their own in significant ways.